Recurrent erythema multiforme with arthritis - A rare association - Yasmeen Jabeen Bhat; Sumaya Zeerak; Asif Nazir Baba; Iffat Hassan; Roohi Wani (Our Dermatology Online, 2017)
Erythema multiforme (EM) is an acute, immune-mediated, self-limiting mucocutaneous condition characterized by distinctive target lesions. The etiology is diverse and numerous diseases have been associated with EM. However, arthritis has been rarely reported with it. We report a rare association between EM, localized mainly over the joints, and polyarthritis in a male patient, who responded successfully to oral acyclovir.